Assessing the development impacts of bio-innovations: The case of genetically modified maize and cassava in Tanzania - Benfica, Rui; Zambrano, Patricia; Chambers, Judith A.; Falck-Zepeda, José B. (International Association of Agricultural Economists, 2024)
Tanzania’s agriculture is characterized by low productivity due to unpredictable rainfall and the prevalence of pests and diseases. Genetically modified (GM) maize offering protection against drought and insects are being developed. Likewise, GM varieties resistant to cassava brown streak disease were developed. Building on prior crop-based analyses, we use the Rural Investment and Policy Analysis (RIAPA) CGE model to assess the impacts of the adoption of those GM crops. GM maize and cassava have positive effects on the economy, the Agri-Food System (AFS), and poverty. Given its stronger linkages in the AFS, the effects of the GM maize are stronger, especially in higher adoption and high yield scenarios. Likewise, the effects on the poorest and rural households are greater. The high variation across scenarios, and the significant effect of the high adoption/high yield scenarios, suggests a high return to investments and policies that realize these adoption rates and yield potential.